2015
DOI: 10.1371/journal.pone.0121419
|View full text |Cite
|
Sign up to set email alerts
|

Renal Intercalated Cells Sense and Mediate Inflammation via the P2Y14 Receptor

Abstract: Uncontrolled inflammation is one of the leading causes of kidney failure. Pro-inflammatory responses can occur in the absence of infection, a process called sterile inflammation. Here we show that the purinergic receptor P2Y14 (GPR105) is specifically and highly expressed in collecting duct intercalated cells (ICs) and mediates sterile inflammation in the kidney. P2Y14 is activated by UDP-glucose, a damage-associated molecular pattern molecule (DAMP) released by injured cells. We found that UDP-glucose increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 76 publications
4
87
0
Order By: Relevance
“…We recently showed that the adenosine receptors ADORA2A and ADORA2B, located in the apical membrane of the collecting duct ICs, stimulate proton secretion via activation of the cAMP/PKA pathway [20]. In this review article, we describe how another member of the purinergic family, the proinflammatory receptor P2Y 14 , mediates renal inflammation via ICs [1], and suggest how this might be applicable to the diagnosis and treatment of AKI.…”
Section: Purinergic Signaling In the Kidneymentioning
confidence: 98%
See 4 more Smart Citations
“…We recently showed that the adenosine receptors ADORA2A and ADORA2B, located in the apical membrane of the collecting duct ICs, stimulate proton secretion via activation of the cAMP/PKA pathway [20]. In this review article, we describe how another member of the purinergic family, the proinflammatory receptor P2Y 14 , mediates renal inflammation via ICs [1], and suggest how this might be applicable to the diagnosis and treatment of AKI.…”
Section: Purinergic Signaling In the Kidneymentioning
confidence: 98%
“…In contrast to most nucleotides, which are rapidly degraded by ectonucleotidases after their release, UDP-glucose resists hydrolysis by these enzymes [25]. P2Y 14 is an inflammatory mediator that is expressed in immune cells [26][27][28], the brain, gastrointestinal tract, kidney, and lungs [1,21,29]. Patients with cystic fibrosis and asthma have elevated concentrations of UDP-glucose in their lungs [30,31], and P2Y 14 activation by UDP-glucose in airway epithelial cells leads to interleukin 8 secretion and an inflammatory response [32].…”
Section: Identification Of the P2y 14 Receptor In Collecting Duct Icsmentioning
confidence: 99%
See 3 more Smart Citations